"Working in the grave" the development of a health and safety system on the Witwatersrand gold mines, 1900-1939 - Smith, Matthew John (Rhodes University, Faculty of Humanities, Department of History, 1993)
This thesis analyses the establishment of a health and safety system on the Witwatersrand gold mines in the period between the end of the South African War and the eve of World War Two. The period has been chosen, firstly, because the South African War had seriously disrupted production and the industry virtually had to start up again from scratch; secondly, because it was during this period that mine and state officials began to seriously investigate the reasons for the appalling mortality and morbidity rates on these mines; and, thirdly, because during this period some improvements did occur which were significant enough to enable the industry to warrant the lifting, in the latter part of the 1930s, of the ban on tropicals, enforced since 1913 as a result of their extremely high mortality rate. In the first thirty years of the twentieth century about 93 000 African miners died disease-related deaths and in the same period some 15000 African miners were killed in work-related deaths. In attempting to establish why so many African miners died, the thesis attempts to identify the diseases and accidents that caused these deaths and considers what attempts were made to bring mortality and morbidity rates down. Whilst the thesis is neither a history of gold mining in South Africa nor an economic history of South Africa in the period 1901 to 1939, it nevertheless, as detailed in the first chapter, places the health and safety system within the context of the wider political and economic forces that shaped the mining industry in this period. The need for a productive and efficient labour force, vital for the industry'S survival during a number of profitability crises in this period, forced the industry to reassess compound structures, nutrition and eventually the health of its work force. These issues of compounds, work and diet are discussed in chapters two, three and four. Appalling living and working conditions led to a high incidence of pulmonary diseases - TB, silicosis and pneumonia - which were the principal killers on the mines. Attempts to cure or prevent their occurrence are discussed in chapter five. Fear of disruptions to production ensured that the mining industry eventually also devoted considerable resources to accident prevention, a theme which is discussed in chapter six. The thesis concludes that the mining industry for much of this period was able to determine the pace of change; neither state officials nor African miners were able to significantly alter the tempo. In fact the industry was so successful that it was able to convince a number of government commissions in the 1940s that the migrant system had to stay, to ensure the wellbeing of the miner. This meant that despite considerable time, money and effort being spent on establishing a health and safety system on the gold mines, the mining industry was still of the opinion that the health of their workers was best served if they were sent home.
Keywords: Gold mines and mining -- South Africa -- Witwatersrand -- Safety measures -- History -- 20th century